Fifteen-Year Trends in Awareness of Heart Disease in Women: Results of a 2012 American Heart Association National Survey - Mosca, Lori (2013)
BACKGROUND: The purpose of this study was to evaluate trends in awareness of cardiovascular disease (CVD) risk among women between 1997 and 2012 by racial/ethnic and age groups, as well as knowledge of CVD symptoms and preventive behaviors/barriers. METHODS AND RESULTS: A study of awareness of CVD was conducted by the American Heart Association in 2012 among US women >25 years of age identified through random-digit dialing (n=1205) and Harris Poll Online (n=1227), similar to prior American Heart Association national surveys. Standardized questions on awareness were given to all women; additional questions about preventive behaviors/barriers were given online. Data were weighted, and results were compared with triennial surveys since 1997. Between 1997 and 2012, the rate of awareness of CVD as the leading cause of death nearly doubled (56% versus 30%; P<0.001). The rate of awareness among black and Hispanic women in 2012 (36% and 34%, respectively) was similar to that of white women in 1997 (33%). In 1997, women were more likely to cite cancer than CVD as the leading killer (35% versus 30%), but in 2012, the trend reversed (24% versus 56%). Awareness of atypical symptoms of CVD has improved since 1997 but remains low. The most common reasons why women took preventive action were to improve health and to feel better, not to live longer. CONCLUSIONS: Awareness of CVD among women has improved in the past 15 years, but a significant racial/ethnic minority gap persists. Continued effort is needed to reach at-risk populations. These data should inform public health campaigns to focus on evidenced-based strategies to prevent CVD and to help target messages that resonate and motivate women to take action.